How to Increase Public Support for Carbon Pricing - Andrej Woerner; Taisuke Imai; Davide Pace; Klaus Schmidt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
The public acceptability of a carbon price depends on how the revenues from carbon pricing are used. In a fully incentivised experiment with a large representative sample of the German population, we compare five different revenue recycling schemes and show that support for a carbon price is maximised by a "Climate Premium" that pays a fixed, uniform, upfront payment to each person. This recycling scheme receives more support than tax and dividend schemes, than using revenues for the general budget of the government, and than earmarking revenues for environmental projects. Furthermore, we show that participants and experts underestimate the public support for carbon pricing.
Keywords: H23; P18; C9; D9; 330; carbon pricing; pigovian taxation; political support for carbon taxes; survey experiments